Verification of a proteomic biomarker panel to diagnose minor stroke and transient ischaemic attack: phase 1 of SpecTRA, a large scale translational study. (19th May 2018) - Penn, Andrew M.; Bibok, Maximilian B.; Saly, Viera K.; Coutts, Shelagh B.; Lesperance, Mary L.; Balshaw, Robert F.; Votova, Kristine; Croteau, Nicole S.; Trivedi, Anurag; Jackson, Angela M.; Hegedus, Janka; Klourfeld, Evgenia; et al.
Abstract: Objective: To derive a plasma biomarker protein panel from a list of 141 candidate proteins which can differentiate transient ischaemic attack (TIA)/minor stroke from non-cerebrovascular (mimic) conditions in emergency department (ED) settings. Design: Prospective clinical study (#NCT03050099) with up to three timed blood draws no more than 36 h following symptom onset. Plasma samples analysed by multiple reaction monitoring-mass spectrometry (MRM-MS). Participants: Totally 545 participants suspected of TIA enrolled in the EDs of two urban medical centres. Outcomes: 90-day, neurologist-adjudicated diagnosis of TIA informed by clinical and radiological investigations. Results: The final protein panel consists of 16 proteins whose patterns show differential abundance between TIA and mimic patients. Nine of the proteins were significant univariate predictors of TIA [odds ratio (95% confidence interval)]: L-selectin [0.726 (0.596–0.883)]; Insulin-like growth factor-binding protein 3 [0.727 (0.594–0.889)]; Coagulation factor X [0.740 (0.603–0.908)]; Serum paraoxonase/lactonase 3 [0.763 (0.630–0.924)]; Thrombospondin-1 [1.313 (1.081–1.595)]; Hyaluronan-binding protein 2 [0.776 (0.637–0.945)]; Heparin cofactor 2 [0.775 (0.634–0.947)]; Apolipoprotein B-100 [1.249 (1.037–1.503)]; and von Willebrand factor [1.256 (1.034–1.527)]. The scientific plausibility of the panel proteins is discussed. Conclusions: Our panel has the potential to assist ED physicians in distinguishing TIA from mimic patients.